Current and Future Perspectives of PD-1/PDL-1 Blockade in Cancer Immunotherapy - Rangarirai Makuku; Neda Khalili; Sepideh Razi; Mahsa Keshavarz-Fathi; Nima Rezaei (Journal of Immunology Research)
Cancer immunotherapy, which reactivates weakened immune cells of cancer patients, has yielded great success in recent years. Among immunotherapeutic agents, immune checkpoint inhibitors have been of particular interest and have gained approval by the FDA for treatment of cancers. Immune checkpoint blockade through targeting programmed cell death protein-1 (PD-1) has demonstrated promising antitumor effects in cancer immunotherapy of many different solid and hematologic malignancies. However, despite promising results, a favorable response is observed only in a fraction of patients, and there is still lack of a single therapy modality with curative ability. In this paper, we review the current and future perspectives of PD-1/L1 blockade in cancer immunotherapy, with a particular focus on predictive biomarkers of response to therapy. We also discuss the adverse events associated with PD-1/L1/2 inhibitors, ranging from severe life-threatening conditions such as autoimmune myocarditis to mild and moderate reactions such as skin rashes, and explore the potential strategies for improving the efficacy of immunotherapy with PD-1/L1 checkpoint inhibitors.